Near-Field Focused Folded Transmitarray Antenna for Medical Applications - Zainud-Deen, Saber H.; Hassan, Walaa M.; Malhat, Hend A. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A near-field focused folded transmitarray antenna is proposed at 2.45 GHz for medical applications. The proposed folded transmitarray construction introduces compact design, low profile, and reduced fabrication cost with focused power in both the near-field and far-field regions of the antenna. The transmitarray consists of a feeding horn antenna embedded centrally in the transmitarray structure and a perfect electric conductor plate with the same size as a reflector. The radiation from the feeding horn is reflected by the plate toward the transmitarray. The unit-cell element of the transmitarray is a square dielectric box with four identical circular holes. The transmission coefficient was nearly -3 dB in magnitude and 320 degrees in phase. The radiation characteristics of the unfolded and folded transmitarray are analyzed using the finite integral technique. The normalized power density distribution around a part of the human leg placed in front of the transmitarray is investigated. The proposed antenna is used to heat a specific area on the human leg for treatment.